Self-Efficacy of Live Streaming Hosts Influenced By Mindset - Sefianmi, Detri; Sari, Rina; Mustika, Rika (Journal of Consumer Studies and Applied Marketing, 2024)
Self-efficacy (Bandura, 1997) reflects the Host's belief in their ability to perform an activity. Furthermore, self-efficacy can influence the host's behavior when facing new challenges and situations. The level of individual self-efficacy is strongly influenced by the individual's ability to cope with the task. This condition is an indication of the form of mindset that affects the level of Host self-efficacy. According to Dweck (Rosyid, 2021), Mindset is the way a person views their ability to understand and face the world. A person's mindset can be seen from his attitude and behavior when responding to events or phenomena he experiences. Dweck (2015) suggests that there are two types of mindset, namely growth mindset and fixed mindset. This study uses quantitative research methods with an inductive approach. Respondents used were 402 Live Streaming Hosts. This research data collection uses a questionnaire distributed via google form. Based on the results of data analysis, it was found that there was a significant positive effect of fixed mindset and growth mindset on the self-efficacy of Live Streaming Hosts in the Kitty Live and Mico applications (R2 .019; sig<0.05 and R2 .020; sig<0.05). When Hosts have a growth mindset, it will increase their confidence in their abilities.